What is the Function of Reasoning? On Mercier and Sperber's Argumentative and Justificatory Theories. (September 2020) - Dogramaci, Sinan
Abstract: This paper aims to accessibly present, and then critique, Hugo Mercier and Dan Sperber's recent proposals for the evolutionary function of human reasoning. I take a critical look at the main source of experimental evidence that they claim as support for their view, namely the confirmation or "myside" bias in reasoning. I object that Mercier and Sperber did not adequately argue for a claim that their case rests on, namely that it is evolutionarily advantageous for you to get other people to believe whatever you antecedently believe. And I give my own argument that this claim is false. I also critically look at their suggestion that reasoning has a justificatory function, functioning as a kind of reputation management tool. I argue this suggestion does not amount to a plausible evolutionary function.